2019 IEEE International Conference on Sensors and Nanotechnology 2019
DOI: 10.1109/sensorsnano44414.2019.8940049
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Concrete Corrosion using EMI Sensor

Abstract: Reinforced Concrete (RC) is globally used to make the building structure strong and more durable. Civil and structural engineers face major challenges as concrete structures deteriorate and get weaker. Recent development in field of assessing and monitoring the health condition of the building structure have shown that corrosion in concrete reinforcement is the cause of failure. Thus, there lies a better research opportunity in the field of monitoring and assessing health condition of the building structure. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Chand et al [29] suggested a new method of HCP measurement by means of two coils functioning according to Faraday's law of electromagnetic induction. Although this approach can hardly become widespread, it demonstrates that researchers today have a wide range of instruments to solve the problem.…”
Section: Half-cell Potential (Hcp) Sensorsmentioning
confidence: 99%
“…Chand et al [29] suggested a new method of HCP measurement by means of two coils functioning according to Faraday's law of electromagnetic induction. Although this approach can hardly become widespread, it demonstrates that researchers today have a wide range of instruments to solve the problem.…”
Section: Half-cell Potential (Hcp) Sensorsmentioning
confidence: 99%